Fluorescence detection of malachite green in fish tissue using red emissive Se, N, Cl-doped carbon dots. (15th January 2021) - Hu, Yaoping; Gao, Zhijin; Luo, Junfei
Highlights: Highly bright, red emissive Se, N, Cl-doped carbon dots are prepared. Carbon dots can be used for trace detection of malachite green in fish tissue. The inner filter effect is proposed to be the main detection mechanism. Abstract: Facile detection of malachite green (MG), a toxic dye, in aquaculture is urgently demanded for environment and food safety. Herein, we design a novel fluorescent probe, namely red emissive Se, N, Cl-doped carbon dots (CDs), to accurately determinate MG. CDs are prepared by hydrothermal treatment of selenourea and o-phenylenediamine in HCl solution. This material exhibits excitation-independent dual emissions at 625 and 679 nm, with a high quantum yield of 23.6%. A selective and sensitive fluorescent sensor toward MG is established based on inner filter effect, because both the excitation and emission light of CDs can be strongly absorbed by MG. The fluorescence quenching of CDs is linear to the MG concentration over the range of 0.07–2.50 μM with a low detection limit of 21 nM. Trace-level analysis of MG in fish tissue is successfully explored, demonstrating the great potential of the proposed sensor for MG monitoring in aquatic products.